2020
DOI: 10.1083/jcb.201904137
|View full text |Cite
|
Sign up to set email alerts
|

Hemidesmosomes modulate force generation via focal adhesions

Abstract: Hemidesmosomes are specialized cell-matrix adhesion structures that are associated with the keratin cytoskeleton. Although the adhesion function of hemidesmosomes has been extensively studied, their role in mechanosignaling and transduction remains largely unexplored. Here, we show that keratinocytes lacking hemidesmosomal integrin α6β4 exhibit increased focal adhesion formation, cell spreading, and traction-force generation. Moreover, disruption of the interaction between α6β4 and intermediate filaments or la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
100
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 103 publications
(128 reference statements)
10
100
0
Order By: Relevance
“…Therefore, the changes observed are expected, since most of the cancer types analysed in Figure 2 are carcinomas developed from epithelial tissues for which the importance of hemidesmosome components in carcinogenesis was recently reviewed [ 59 ]. Moreover, recently published data by Wang and colleagues [ 14 ] revealed a novel role for HDs as regulators of cellular mechanical forces. They showed the existence of a mechanical coupling between different IACs, specifically HDs and FAs and RAs.…”
Section: The Integrin Repertoire Is Changed or ”Switched” In Cancementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the changes observed are expected, since most of the cancer types analysed in Figure 2 are carcinomas developed from epithelial tissues for which the importance of hemidesmosome components in carcinogenesis was recently reviewed [ 59 ]. Moreover, recently published data by Wang and colleagues [ 14 ] revealed a novel role for HDs as regulators of cellular mechanical forces. They showed the existence of a mechanical coupling between different IACs, specifically HDs and FAs and RAs.…”
Section: The Integrin Repertoire Is Changed or ”Switched” In Cancementioning
confidence: 99%
“…Upon integrin binding and clustering, proteins are recruited to their cytoplasmic tails to form multimolecular integrin adhesion complexes (IACs), the composition of which has been termed the adhesome. Excellent reviews have been published describing integrin structure and function, as well as IAC composition [ 3 , 4 , 5 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. These reviews also highlight the versatility of integrin family and its contribution to different aspects of cell behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of different proteins are associated with FAs in different contexts; however, at the core of LM332 bound adhesions is the adaptor protein paxillin, which plays a scaffolding role through supporting recruitment of multiple other proteins (Ofuji, 2000;Turner, 2000). There is extensive cross-talk between HDs and FAs and recently it has been shown that this crosstalk is also relevant for force generation (Hopkinson et al, 2014;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This in contrast to the interaction between CMSCs and FAs, which is mediated by the binding of KANK to talin in FAs ( Bouchet et al, 2016 ). Recently, we showed that in keratinocytes, FAs and HDs are localized in close proximity to each other and that plectin plays a critical role in the mechanical coupling of these two adhesion structures ( Wang et al, 2020 ). Hence, we believe that the localization of CMSC near HDs is due to the interaction of CMSC with the HD-associated FAs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that FAs and HDs are mechanically coupled, and that plectin, which binds integrin β4 and F-actin in a mutually exclusive manner, plays a central role in this coupling ( Wang et al, 2020 ). In this study, we used proximity dependent biotinylation (BioID) ( Roux et al, 2012 ) to map the interactomes of the integrin α6 and β4 subunits in keratinocytes and assessed the contribution of CD151 to the β4 interactome.…”
Section: Introductionmentioning
confidence: 99%